Evaluasi Respons Hukum Humaniter Internasional terhadap Perang Siber - Aristyawati, Dhita Evany; Uyun, Rohmatun; Nugroho, Adelia Zahra (Indonesian Journal Publisher, 2024)
Cyberwarfare is a form of warfare that cannot be explicitly addressed by existing international law. While most experts agree that legal restrictions must apply to this phenomenon, However, the international community has not been able to reach a consensus on how international humanitarian law (IHL) can be adapted. After outlining several cyber conflicts, this article argues that this issue is still unresolved academically. We use descriptive research methods to look for adequate and sufficient descriptions of processes, objects, activities, and people. Some parts of the Hague Convention and the Geneva Convention may indeed be relevant to cyber warfare, but their specific relevance cannot respond to this phenomenon. This is confirmed by the emergence of the virtual world, which is more recent when compared to the birth of the instrument. Many cyberattacks unavoidably result in losses for the parties, making these breaches more likely in cyber conflicts than in conventional wars. States have strong incentives to engage in cyberattacks, despite the risk of being accused of war crimes. With this in mind, this article also argues that IHL should evolve to encourage the creation of a legal umbrella against cyber warfare in some situations and provide better guidance for states in carrying out these types of attacks.